Microbial Biofilms - Importance and Applications 2016
DOI: 10.5772/62803
|View full text |Cite
|
Sign up to set email alerts
|

Novel Models to Manage Biofilms on Microtextured Dental Implant Surfaces

Abstract: Dental implants are used extensively to replace missing teeth. To enhance their integration with the bones of the jaws, the surfaces of titanium dental implants are modified to make them hydrophilic, high energy, and microtextured. These same features make biofilm development occur readily upon exposure to the saliva. The presence of mature biofilms on dental implant surfaces drives local inflammatory responses in the adjacent soft and hard tissues (peri-implantitis), which leads to pathological loss of bone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The BHI salivary inoculum model was chosen to mimic an exposed root canal in the oral cavity. Prior studies using this model in the laboratory had shown that the salivary inoculum contained a diverse range of oral bacteria, as shown by Next-Gen sequencing [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The BHI salivary inoculum model was chosen to mimic an exposed root canal in the oral cavity. Prior studies using this model in the laboratory had shown that the salivary inoculum contained a diverse range of oral bacteria, as shown by Next-Gen sequencing [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…This should mimic, at least in part, the polymicrobial nature of biofilms in endodontic infections [34]. Our past work has indicated that biofilms can develop in the root canal in this time frame of 7 days [35][36][37], and that low oxygen conditions during this time facilitate the growth of a diverse flora with anaerobes from a saliva inoculum [38]. Having said this, the situation is not the same as when bacteria colonise the root canal and survive for long periods of time.…”
Section: F I U R Ementioning
confidence: 99%
“…The physical removal of bacterial biofilms from titanium implant surfaces is the simplest and oldest form of treatment. Initially, hand-operated scalers and then powered (ultrasonic) scalers were used, and more recently particle beams were deployed [ 26 ]. A concern with all physical debridement methods is the extent of surface damage they cause.…”
Section: Surface Cleaning Techniquesmentioning
confidence: 99%